Bacterial microflora of the upper gastrointestinal tract in infants with protracted diarrhoea. Issue 4 (April 1974) - Challacombe, D. N.; Richardson, Judith M.; Rowe, B.; Anderson, Charlotte M.
Abstract : The aerobic and anaerobic bacterial microflora of the upper gastrointestinal tract in infants with protracted diarrhoea has been described and compared with a group of control infants without diarrhoea. The duodenal juice of patients with protracted diarrhoea was rarely sterile and was characterized by an increase in numbers and types of microorganisms and by the presence of coliforms, particularly Esch. coli. In individual patients the same serotypes of Esch. coli were found throughout the intestinal tract. The presence of Esch. coli in the upper small intestine may be as important to the aetiology of protracted diarrhoea as it is to acute diarrhoea.